2007
DOI: 10.1097/ajp.0b013e318065b6c9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Acute Herpes Zoster Pain and Discomfort on Functional Status and Quality of Life in Older Adults

Abstract: Acute zoster pain and discomfort has a significant negative impact on functional status and HRQL in older adults. The magnitude of interference increases with increasing pain and discomfort intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 17 publications
9
111
1
1
Order By: Relevance
“…13 Our results are consistent with those findings, although they only reached statistical significance for pain lasting 30 d. The importance of the findings regarding prevention of PHN derives from the fact that the main health and non-health burdens associated with HZ are due to PHN, which significantly decreases quality of life by affecting mobility, self-care, usual activities, or social life 20,21 whereas available pain medications and neuropathic treatments are only modestly effective for controlling PHN pain. 7 To fully understand the impact of HZ vaccine, besides determining the proportion of HZ or PHN cases prevented, it is important to understand the characteristics and sequelae of HZ that occurs in vaccinated persons compared with unvaccinated.…”
Section: Discussionsupporting
confidence: 85%
“…13 Our results are consistent with those findings, although they only reached statistical significance for pain lasting 30 d. The importance of the findings regarding prevention of PHN derives from the fact that the main health and non-health burdens associated with HZ are due to PHN, which significantly decreases quality of life by affecting mobility, self-care, usual activities, or social life 20,21 whereas available pain medications and neuropathic treatments are only modestly effective for controlling PHN pain. 7 To fully understand the impact of HZ vaccine, besides determining the proportion of HZ or PHN cases prevented, it is important to understand the characteristics and sequelae of HZ that occurs in vaccinated persons compared with unvaccinated.…”
Section: Discussionsupporting
confidence: 85%
“…For example, in a French study of HZ in general practice (ARIZONA), 80% of the patients received treatment but 10% had PHN at 1 year [18,26]. A specific tool, the Zoster Brief Pain Inventory (ZBPI) has been developed to measure the impact of HZ/PHN-related pain and discomfort on seven general activities: work, sleep, walking, life enjoyment, mood, relations with others and general activity [20,27,28]. The results in the placebo group of a zoster vaccine clinical trial showed that the impact on ADL increased with age, and the impact continues after resolution of pain [20,29] (Fig.…”
Section: Vaccine-preventable Infectious Diseases That Contribute To Cmentioning
confidence: 99%
“…This is likely to be true for influenza and pneumococcal pneumonia that can be associated with serious complications and lead to hospitalization. Their effective prevention would prevent functional decline and improve the health span of older adults [18,20,27,28,32].…”
Section: Strategies For Improving Vaccination Effectiveness In the Elmentioning
confidence: 99%
“…Often reported sequelae of PHN comprise sleeping problems, chronic fatigue, anorexia, weight loss and depression, resulting in substantial interference with social life and self-care. 4,14,16,17 In 2006, a VZV vaccine with the tradename Zostavax® (Sanofi-Pasteur/MSD) was approved by the US Food and Drug Administration (FDA) as well as by the European Medicines Agency (EMA). 18,19 Zostavax® contains a live attenuated strain of VZV and is thought to induce primarily T-cell-mediated immunity against VZV.…”
Section: Introductionmentioning
confidence: 99%